One class of Nash equilibria in bimatrix games - Aneta Gracjana Blaževič; Daina Sūdžiūtė (Lietuvos Matematikos Rinkinys)
Active Nash equilibria existence in bimatrix game problem is reduced to the problem of nonexistence of special solutions of the systems (11) and (12).